2019
DOI: 10.1292/jvms.18-0581
|View full text |Cite
|
Sign up to set email alerts
|

The bacterial load in milk is associated with clinical severity in cases of bovine coliform mastitis

Abstract: We evaluated the relationship between the severity of coliform mastitis and bacterial load in 106 quarter milk samples. We found no significant relationship between somatic cell count and coliform bacterial load in milk in bovine clinical coliform mastitis. Results of the Cochran-Armitage test for trend in milk bacterial load proportions indicated a significant decreasing low group (P<0.001), increasing medium group (P<0.002) and increasing high group (P<0.02) with increasing clinical grade. The present study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 43 publications
0
19
0
Order By: Relevance
“…E. coli and Klebsiella spp. are known to be the major pathogens causing coliform mastitis (Klaas & Zadoks, 2018;Nagasawa et al, 2019). It is generally known that mastitis caused by Klebsiella spp.…”
Section: Discussionmentioning
confidence: 99%
“…E. coli and Klebsiella spp. are known to be the major pathogens causing coliform mastitis (Klaas & Zadoks, 2018;Nagasawa et al, 2019). It is generally known that mastitis caused by Klebsiella spp.…”
Section: Discussionmentioning
confidence: 99%
“…We have already reported that although the clinical score for coliform mastitis is unrelated to the somatic cell count, it is related to coliform bacterial counts [ 14 ]. The results of this study were similar to those of previous reports and also showed an association between clinical scores and ICS test scores.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the ICS test is effective only for the identification of a specific bacterial species, but it is considered to be useful when quickly determining the causative bacterial species is necessary [ 15 ]. Coliform bacterial load in milk is significantly associated with the clinical severity of coliform mastitis in cows and is considered a useful indicator for its optimal management [ 14 ]. In the ICS test, the time for result determination was one hour, which included the time for bacteriolysis and reaction; however, we were able to obtain the results as quickly as 30–40 min for milk samples from severe cases with high coliform counts.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations